CHANGE OF PROFESSIONS AND SKILLS IN THE FIELD OF TOURISM UNDER THE INFLUENCE OF ARTIFICIAL INTELLIGENCE (Scientific electronic journal "Labor Economics and Human Capital", 2024)
Last few years, Uzbekistan has been paying great attention to the development of the tourism sector in the conditions of digital economy and AI.  Because, today and in the near future, the effectiveness of the tourism sector will depend mainly on digital technologies and artificial intelligence. This study combines a set of approaches, including literature review, analysis of related data as well as comparison with others countries to show the impact of AI on the job market and required skills on tourism. The central point in this research paper is to look through how Artificial Intelligence is reshaping tourism in terms of the skill requirements, job hierarchy and the overall structure alongside with the current position of Uzbekistan in this sector. Standardization, Metrology, and Certification Agency of Uzbekistan (documented in the Ministry of Justice’s decree, account number 15, on May 22, 2021) are changing on and off site work requirements and essential skills, reflecting these interventions done by AI. Moreover, this research combines necessary data on the employment of workforce as well as occupational distribution trends. Another significance in this paper is the availability of real-time observation of labor demands and the changing face of skill sets taken from the leading job platforms. This broad and in-depth approach can definitely help professionals who are working or about to work in this sphere a clear picture of how AI is affecting all the way from the bottom of the job hierarchy to the top.
Keywords: Occupations, Work requirements, impact of AI to qualifications, job platforms.